Evaluation of Preoperative and Postoperative Anxiety Levels of Patient Relatives in Patients Undergoing Anesthesia for Surgical Operation - İlker İnce; Kamber Kaşali; Aysenur Dostbil; Mehmet Aksoy; İrem Ateş; Özgür Özmen; Mehmet Sercan Orbak (Trends in Surgical Sciences, 2025)
Objective: Using the STAI anxiety scale, patient relatives; We aimed to evaluate preoperative, intraoperative and postoperative anxiety levels according to age, gender, familiarity levels, education, professions, anesthesia experience and type of surgery.Methods: Preoperative, intraoperative and postoperative advice to the relatives of patients who will undergo surgery; The "STAI FORM TX-1" survey form, which is used to measure situational anxiety, was filled out according to the patient's relatives' age, gender, level of closeness with the patient, educational status, profession, anesthesia experience, type of surgery that the patient will undergo and their level of preoperative information.Results: Each group is formed according to preoperative, intraoperative and postoperative patient age, gender, ASA, surgery type, surgery duration, anesthesia type, patient relative age, patient relative gender, past anesthesia experience, degree of closeness, frequency of meeting with the patient, education level and income level. When compared, there was a statistically significant difference in all groups except the group with patient age >74 and the group whose degree of closeness to the patient was the mother (P < .05). When all groups were evaluated within themselves, male gender was statistically significant for anxiety generation in terms of patient gender (P < .05). Conclusion: It has been observed that there are multiple factors that can cause anxiety in patients' relatives. It has been observed that the intraoperative anxiety of patient relatives with high preoperative anxiety levels increases, and postoperatively, it decreases from preoperative levels.